REMOTE COLLABORATION AND MONEY TRANSFER TECHNOLOGIES: IMPROVING BANK SERVICES AND FACILITATING FINANCIAL OPERATIONS (Intent Research Scientific Journal, 2023)
The article analyzes the use of remote cooperation and money transfer technologies by banks and their role in improving their services and facilitating financial transactions. The article discusses the importance of remote cooperation for banks and its benefits. Remote cooperation technologies, such as mobile applications, internet banking, electronic payment systems, etc., facilitate communication between banks and customers and make services more convenient. The article highlights the importance of cash flow technologies in facilitating and improving financial transactions for banks. These technologies, such as automatic payment systems, electronic settlement systems, blockchain, etc., speed up financial transactions, reduce errors and increase security. The article also points out the problems associated with remote collaboration and coin-tossing technologies. These issues include security issues, technological errors, trust issues between customers and banks, personal data protection, and more.